Electrophilic Aromatic Trifluoromethylthiolation with the Second Generation of Trifluoromethanesulfenamide - Alazet, Sébastien; Billard, Thierry (Synlett, 2015)
Direct trifluoromethylthiolation of various aromatic and heteroaromatic compounds, variously substituted, can be performed with the second generation of trifluoromethanesulfenamide via a ‘Friedel–Crafts-like reaction’. This reaction requires mild conditions with a catalytic amount of protic or Lewis acid. Good results have been obtained, even with aromatic compounds bearing deactivating substituents.
Keywords: trifluoromethylthiolation; fluorine; arenes; heterocycles; trifluoromethanesulfenamide